Pengaruh Prosedur Orientasi terhadap Tingkat Kecemasan pada Pasien yang Menjalani Terapi Oksigen Hiperbarik (TOHB) di Rumah Sakit Paru Jember - Pravita Dwi Ariyani; Dodi Wijaya; Ahmad Rifai (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Hyperbaric oxygen therapy is a treatment method in patients with inhaling pure oxygen at pressuresgreater than normal atmospheric pressure. Patients who first followed the hyperbaric therapy willgenerally feel anxiety due to side effects of hyperbaric therapy. Orientation procedure can be used todecrease level of anxiety of patients. The purpose of this study was to analyze the effect of theorientation procedure on the level of anxiety of patients undergoing hyperbaric oxygen therapy atRumah Sakit Paru Jember. The design of study was pre experimental design with one group pretestand post test. The sampling technique was consecutive sampling involving 32 respondents. Datawere analyzed with Wilcoxon Test. The result showed a significant decrease of moderate anxiety tomild anxiety with implementation of orientation procedure (p=0.000). It can be concluded that thereis an effect of the orientation procedure on the level of anxiety of patients undergoing hyperbaricoxygen therapy at Rumah Sakit Paru Jember. The provision of adequate information and theintroduction of a hyperbaric chamber every corner of the room so that the patient is able to adapt tothe first experience, so that the necessary role of nurses in assisting the patient to provide referralsfor patients who want to undergoing hyperbaric therapy in order to follow the therapy process untilcomplete. Orientation procedure of hyperbaric therapy can be applied as one of method to decreaselevel of anxiety of patients undergoing hyperbaric oxygen therapyKeywords: orientation procedure, hyperbaric oxygen therapy, level of anxiety